United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Anti-Money Laundering/Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2010)
The Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) regime of the United States is overviewed. The United States has implemented a system that is broadly in line with the international AML/CFT standard. However, many of the recommendations made by the evaluators to address the identified deficiencies have not been addressed, but efforts are under way; notably to introduce a uniform legislation that would require information on beneficial ownership and control of legal persons and arrangements across all the states.